Reporting quality of pilot clinical trials in chronic kidney disease patients on hemodialysis: a methodological survey - Kosa, Sarah Daisy (Pilot Feasibility Stud, 2019)
BACKGROUND: The conduct of high-quality pilot studies can help inform the success of larger clinical trials. Guidelines have been recently developed for the reporting of pilot trials. OBJECTIVE: This methodological survey evaluates the completeness of reporting in pilot randomized controlled trials in chronic kidney disease patients on hemodialysis (HD patients) and explores factors associated with better completion of reporting. METHODS: The authors searched Pubmed on July 1, 2018, for all pilot trials conducted in HD patients. Reporting quality was assessed against the 40-item Consolidated Standards of Reporting Trials (CONSORT) Extension for Pilot Trials. Study factors including year and country of publication, intervention, number of centers, type of funding, and journal endorsement of CONSORT were also examined. RESULTS: The mean number of items reported from the CONSORT extension for pilot trials across all included articles was 18.4 (standard deviation [SD] = 4.4). In the adjusted analysis, studies reported in later years (IRR = 1.026, 95% CI [1.018, 1.034], p < 0.001) and an increase of 20 persons in sample size (adjusted IRR = 1.021, 95% CI [1.010, 1.031], p < 0.001) were associated with a significantly higher number of CONSORT pilot items reported. CONCLUSIONS: Current reporting completeness of pilot trials in HD patients is suboptimal. Endorsing the CONSORT extension specific to pilot and feasibility studies and ensuring that pilot trials focus on the feasibility objectives may improve reporting completeness of these trials. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40814-019-0436-3) contains supplementary material, which is available to authorized users.